2015
DOI: 10.1007/s10096-015-2402-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences between endocarditis caused by Streptococcus bovis and Enterococcus spp. and their association with colorectal cancer

Abstract: Streptococcus bovis group and Enterococcus spp. share phenotypic characteristics and intestinal habitat. Both have been associated with endocarditis and colorectal neoplasm (CRN). We studied all cases of endocarditis diagnosed between 1988 and 2014 in our centre and caused by S. bovis (109, 48.8 % of the bacteremia) and by Enterococcus spp. (36, 3.4 % of the bacteremia). Patients were seen until death or during a long-term follow-up, in order to rule out a concomitant CRN. The 109 cases of S. bovis endocarditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 39 publications
2
29
0
9
Order By: Relevance
“…Corredoira and colleagues demonstrated, in their study, that 21% of patients with enterococcal IE had a new colorectal neoplasm, while in another study, colorectal cancer was detected in more than half of patients with E. faecalis endocarditis with an unknown source of infection . Although possible associations between colon cancer and enterococcal endocarditis have been reported in the literature, robust evidence is lacking. We demonstrated high frequencies of underlying diseases involving the gastrointestinal tract, urological tract and cardiovascular system, as well as malignancies in patients with enterococcal bacteraemia, similar to previous studies …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Corredoira and colleagues demonstrated, in their study, that 21% of patients with enterococcal IE had a new colorectal neoplasm, while in another study, colorectal cancer was detected in more than half of patients with E. faecalis endocarditis with an unknown source of infection . Although possible associations between colon cancer and enterococcal endocarditis have been reported in the literature, robust evidence is lacking. We demonstrated high frequencies of underlying diseases involving the gastrointestinal tract, urological tract and cardiovascular system, as well as malignancies in patients with enterococcal bacteraemia, similar to previous studies …”
Section: Discussionsupporting
confidence: 90%
“…Our findings are supported by several other studies; Sun and colleagues found that patients with IE were at higher risk of underlying colorectal cancer and other malignancies compared with patients without IE . Corredoira and colleagues demonstrated, in their study, that 21% of patients with enterococcal IE had a new colorectal neoplasm, while in another study, colorectal cancer was detected in more than half of patients with E. faecalis endocarditis with an unknown source of infection . Although possible associations between colon cancer and enterococcal endocarditis have been reported in the literature, robust evidence is lacking.…”
Section: Discussionsupporting
confidence: 52%
“…Due to the overwhelming clinical association, it is recommended that patients with Sg infections undergo thorough colon examination. In addition, recent prospective studies followed patients with endocarditis due to Sg or other pathogens for several years and found that a significantly higher percentage of Sg endocarditis patients developed new colonic neoplasm during the follow-up period, compared to patients with endocarditis caused by other pathogens [33,34]. This suggests that Sg plays a role in the early stages of tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…В 1980-2000 годах в ряде исследований, в том числе нескольких небольших исследованиях «случай-контроль» и их метаанализе, было показано, что ИЭ, вызванный Streptococcus gallolyticus (ранее bovis), ассоциируется с карциномой толстой кишки [10][11][12][13][14][15][16], а также были опубликованы описания отдельных случаев и малых серий наблюдений ИЭ у больных с другими онкологическими заболеваниями [17]. Однако наиболее значимые доказательства, подтверждающие ассоциацию ИЭ с онкологическими заболеваниями, были опубликованы за последние 5 лет: 5 крупных популяционных контролируемых исследований и 1 метаанализ, включившие суммарно более 4500 больных ИЭ, у которых при наблюдении разной длительности были диагностированы онкологические заболевания [18][19][20][21][22][23]. В рекомендациях Европейского общества кардиологов 2015 г. ИЭ у онкологических больных выделен как особая форма заболевания [24].…”
unclassified
“…К настоящему времени можно считать в наибольшей степени изученным и доказанным непосредственный и отдаленный высокий риск диагностики опухолей ЖКТ, особенно рака толстой и прямой кишки, при ИЭ, вызванном S. gallolyticus (ранее S. bovis) [20,28,29]. S. bovis относится к стрептококкам группы D и является преобладающим видом в подвздошной кишке человека.…”
unclassified